Pengaruh Penurunan Pajak Pertambahan Nilai (PPN) dan Gaya Hidup Terhadap Minat Pembelian Mobil Bersubsidi di Kota Yogyakarta - Dewi Kusuma Wardani; Setia Fany Anggraeni Pratiwi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Study seeks to analyze the effect of VAT reduction, lifestyle and social environment on the interest in buying subsidized cars in the city of Yogyakarta. This study utilizes quantitative descriptive research and collects primary data through the use of questionnaires. The study includes 140 respondents working in Yogyakarta city. Sampling methodology in this study involved snowball sampling. Data analysis is multiple regression analysis. This study provides results that the decrease in VAT has no effect on the interest in buying subsidized cars, while the lifestyle and social environment of consumers have a positive effect on the interest in buying subsidized cars